0000 to 8085 : Introduction to Microprocessors for Engineers and Scientists - Ghosh, P.K.; Sridhar, P.R. (New Delhi PrenticeHall of India Private Limited, 2004)
Introduction 0000 to 8085, microprocessors, microprocessors for engineers .
Keywords: Microprocessor, MIcrocomputer,microcontroller004.16; Microprocessors, Computer Science